Advance care planning in rehabilitation: An implementation study - Krystal Song; Bhasker Amatya; Fary Khan (Medical Journals Sweden, 2018)
Objective: To identify implementation and process issues that influence the implementation of an advance care planning (ACP) programme in rehabilitation settings. Methods: An ACP programme was established in an inpatient tertiary rehabilitation setting in Victoria, Australia. Rehabilitation patients with chronic illnesses were recruited and the Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework used. Pre-implementation measures included: patient medical record audit of ACP discussions; and barriers and facilitators analyses. Implementation interventions were staff group educational sessions and clinical process changes. Further medical record audit was carried out to review the number of ACP conversations performed and re-evaluate ACP barriers. Results: A total of 180 consecutive inpatients were recruited for pre- (n = 90) and post- (n = 90) implementation groups. The majority of the pre-implementation cohort were female (51%), mean age 64.2 years (standard deviation 16.4 years) and had low rates of ACP discussions (n = 9, 10%). Major ACP barriers included: lack of staff education programme, and insufficient knowledge to conduct ACP. There was a significant increase in ACP conversations performed (n = 21, 23.3%) between both groups; however, staff reported limited time and skills to perform discussions. Conclusion: This ACP programme is feasible, but needs robust process evaluation and longer term follow-up to assess the impact of outcomes in public hospital settings on care quality.